Review of Phytographical Studies on Nepal Himalayas - Bhargava, Ashok Kumar; Kumar, Satendra (Indian Forester, 1976)
Himalayan region or Nepal Kingdom is the meeting place of Western, Eastern, Tibetan and Indian Vegetation, which makes the plant collectors, botanists, horticulturists attraction very much. Nepal's geographical position between Indian Himalayas on two side attracts us to know its phytography, so that a linked relationship may be established between hills of Kumaon and Assam.